Kepemimpinan Keluarga dalam Al-Qur’an dan Transformasi Relasi Keluarga Perkotaan: Perspektif Tafsir Al-Azhar Karya Hamka - Nurhamida Hasibuan (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The dynamics of urban family relations demonstrate shifts in authority, role negotiations, and the intensification of equality values ​​that often clash with Qur’anic norms regarding family leadership. The focus of this study is the concept of qiwāmah in Hamka’s Tafsir al-Azhar and its relevance in a pluralistic, complex modern context. A qualitative approach based on literature studies is used, employing thematic and contextual interpretation analysis to examine verses on family leadership and Hamka’s interpretation within a socio-cultural framework. The results of this study reinterpret qiwāmah as ethical leadership grounded in responsibility, moral capacity, and competence, rather than in gender-based structural domination. Hamka’s interpretation displays conceptual flexibility that creates space for a proportional distribution of roles in urban families, while emphasizing the principles of justice, deliberation, and collective responsibility. The dialectic between text and context demonstrates the integration of Qur’anic normative values ​​with contemporary social realities through adaptive readings that maintain the substance of the teachings without ignoring social change. These findings strengthen the position of contextual interpretation as an approach capable of bridging the tension between religious norms and the transformation of the modern family, while also providing theoretical contributions to the development of thematic interpretation studies and Islamic family studies in the global urban landscape.